Biotechnology and bioengineering: research results from the Faculty of Health Sciences (2024)
The book titled “Biotechnology and Bioengineering: Research Results from the Faculty of Health Sciences” brings together a collection of research studies that highlight the advancement of these disciplines in the health field. Each chapter addresses fundamental and applied topics aimed at solving contemporary problems through science and innovation. The first topic, “Characterization of Antifungal Resistance in Colombian Isolates of Malassezia spp.”, explores the resistance mechanisms of these microorganisms, which are common pathogens in various dermatological conditions. This study has a direct impact on improving therapeutic treatments for fungal infections, particularly in the Colombian context.